2008
DOI: 10.1007/s11295-008-0185-6
|View full text |Cite
|
Sign up to set email alerts
|

A genomewide admixture mapping study for yield factors and morphological traits in a cultivated cocoa (Theobroma cacao L.) population

Abstract: The selection of productive varieties of modern Criollo cocoa, showing fine aromatic qualities in their beans, is of major interest for some producing countries, such as Venezuela. Cultivated populations of Modern Criollo or Trinitario varieties may be suitable for admixture mapping analysis, as large blocks of alleles derived from two identified divergent ancestors, recently admixed, are still preserved, after a few generations of recombination, similar to experimental mapping progenies. Two hundred and fifty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 38 publications
(31 reference statements)
3
17
0
1
Order By: Relevance
“…We demonstrate how these differences in sample-wide LD can practically impact the resolution of association mapping analyses. Using microsatellite haplotypes and phenotypic data on pod coloration, a wellunderstood cacao phenotype (Marcano et al 2008;Motamayor et al 2013), we show how association mapping analyses are far less precise in an F1-mapping population from Brazil (referred to as MP01) compared to a semi-cultivated population from Hawaii (referred to as Hawaii). Finally, given the existence of varying levels of LD in wild and cultivated cacao varieties, we highlight how careful sample selection will be a crucial factor in the efficacy of future association mapping analyses.…”
Section: Communicated By D Grattapagliamentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrate how these differences in sample-wide LD can practically impact the resolution of association mapping analyses. Using microsatellite haplotypes and phenotypic data on pod coloration, a wellunderstood cacao phenotype (Marcano et al 2008;Motamayor et al 2013), we show how association mapping analyses are far less precise in an F1-mapping population from Brazil (referred to as MP01) compared to a semi-cultivated population from Hawaii (referred to as Hawaii). Finally, given the existence of varying levels of LD in wild and cultivated cacao varieties, we highlight how careful sample selection will be a crucial factor in the efficacy of future association mapping analyses.…”
Section: Communicated By D Grattapagliamentioning
confidence: 99%
“…The Pod color phenotype in cacao have been mapped to LG 04 in various genetic backgrounds, including the MP01 population (Motamayor et al 2013), using both family-based linkage and association mapping approaches Marcano et al 2008;Motamayor et al 2013). In the most recent of these studies, extensive analysis of the trait led to the identification of four SNP variants (between 20,878,891 and 20,879,148 bp) within a MYB transcription factor gene (TcMYB113), which are strongly believed to affect pod color differences between cacao varieties (Motamayor et al 2013).…”
Section: Ld Decay and Association Mapping In Two Cacao Populationsmentioning
confidence: 99%
“…Guiltinan (2007) and Clement et al (2004) described the value of the recently constructed cacao bacterial artificial chromosome (BAC) libraries for gene discovery in cacao. Marcano et al (2009) reported on a genome-wide mapping study for yield factors and morphological traits in cacao. Lanaud et al (2009) presented their findings on a meta-QTL analysis of resistance traits to Phytophthora spp.…”
Section: Molecular Approaches: Application Of Genomic Tools Gene Dismentioning
confidence: 99%
“…Clone T1 has a higher estimated maximum annual number of pods per tree than the 36 to 40 reported by Philips‐Mora et al () and Ndoumbè‐Nkeng et al (). However, Marcano et al () have reported very high values of 72 pods per tree per year. This would result in a maximum DPI value around 518 assuming no disease losses.…”
Section: Discussionmentioning
confidence: 98%